Representasi Penulisan Berita Efektif Pada Teras Berita Surat Kabar (Analisis Wacana Pada Film The Bridgerton) - Fitri Nur Ardiantika (Jurnalistik dan Media, 2024)
The Bridgerton film is a British film based on a novel by Julia Quinn, who is known as a writer of historical romance stories. The Bridgerton takes place in England during the Regency era, namely around the 1800s. This film depicts the life of British aristocrats during the Regency Era in England which lasted from 1811 – 1820. The main characters in this film are the Bridgerton family and the writer of the newspaper "Lady Whistledown". Lady Whistledown is the pen name of the writer of the newspaper "Lady Whistledown", who is known as a writer of gossip and information that occurs in the lives of nobles, one of which is the life of The Bridgerton family. Lady Whistledown's newspaper is what the British people are most looking forward to because of its interesting news content, which is needed by certain groups of people and also the writing style is critical and straight to the point. Therefore, Lady Whistledwon's newspaper has unusual news value and human interest. Keywords: Film,Value,News,Writing,Effective